2015
DOI: 10.1080/03602559.2014.974282
|View full text |Cite
|
Sign up to set email alerts
|

Latent Heat Enhancement of Paraffin Wax in Poly(divinylbenzene-co-methyl methacrylate) Microcapsule

Abstract: The preparation of divinylbenzene (DVB)-methyl methacrylate (MMA) copolymer microcapsule encapsulated Rubitherm27 (RT27) P(DVB-co-MMA)/RT27 used as heat storage material by the microsuspension polymerization was studied to improve the latent heats of the encapsulated RT27 with sufficient polymer shell strength. Percent loading of RT27 and DVB:MMA ratio were optimized. The optimal condition was 30% loading of RT27 and 30:70 (% w/w) of DVB:MMA ratio. The nonspherical microcapsules with a dent having core-shell m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The ratio of DVB and styrene was optimized at the weight ratio of 30:70 to improve the latent heats of the encapsulated paraffin wax with sufficient polymer shell strength. The group reported that the thermal properties of RT27encapsulated with copolymer using DVB and styrene was ΔHm = 153 kJ/kg and ΔHc = 164 kJ/kg, which is much higher than those encapsulated using only DVB (ΔHm = 127 kJ/kg and ΔHc = 133 kJ/kg) and closed to bulk RT27 (ΔHm = 162 kJ/Kg and ΔHc = 168 kJ/kg) [5]. Taegu Do et al reported that the fabrication of hydrophilic poly (2-hydroxyethyl methacrylate) (pHEMA) encapsulated paraffin-wax sphere as the PCM capsule with high encapsulation ratio and thermal storage capability.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The ratio of DVB and styrene was optimized at the weight ratio of 30:70 to improve the latent heats of the encapsulated paraffin wax with sufficient polymer shell strength. The group reported that the thermal properties of RT27encapsulated with copolymer using DVB and styrene was ΔHm = 153 kJ/kg and ΔHc = 164 kJ/kg, which is much higher than those encapsulated using only DVB (ΔHm = 127 kJ/kg and ΔHc = 133 kJ/kg) and closed to bulk RT27 (ΔHm = 162 kJ/Kg and ΔHc = 168 kJ/kg) [5]. Taegu Do et al reported that the fabrication of hydrophilic poly (2-hydroxyethyl methacrylate) (pHEMA) encapsulated paraffin-wax sphere as the PCM capsule with high encapsulation ratio and thermal storage capability.…”
Section: Introductionmentioning
confidence: 99%
“…A phase change material changes its state from solid to liquid state due to gaining of thermal energy and changes from liquid to solid due to release of energy via latent heat storage concept. Phase change materials are categorized into (i) organic-paraffin (C n H 2n+2 ) and non-paraffin, (ii) inorganic-salt hydrates (M n H 2 O) and (iii) eutectic,-a combination of organic and inorganic compounds [5,6]. Paraffin waxes are the most common PCM for thermal management having a high heat of fusion per unit weight (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations